2019
DOI: 10.1097/mpa.0000000000001313
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Contributes to Extreme Thrombocytosis After Pediatric Pancreatectomy With Islet Autotransplantation

Abstract: Objective This study aims to explore the role of thrombopoietin (TPO) production in extreme thrombocytosis that is often observed after pancreatectomy with islet autotransplantation (IAT) and the effectiveness of hydroxyurea in thrombocytosis management. Methods Retrospective chart review was performed for all patients who underwent pancreatectomy with IAT at our institution between April 1, 2015, and December 31, 2016. Data evaluated included demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…[34][35][36][37][38] In the TPIAT literature, one small study showed a universal increase in thrombopoietin a few days after surgery, followed by a marked platelet count rise. 16 The data presented here in association with the IBMIR and thrombopoietin production physiology described above suggest that the observations of nearly universal post-TPIAT thrombocytosis likely occurs through both increased proinflammatory platelet production and postsplenectomy mechanisms. 16 Previous work has examined the utility of drugs like heparin, 21 lowmolecular-weight dextran sulfate, 22,39 and melagatran 33 in TPIAT but primarily evaluated whether they reduce IBMIR and thus improve islet survival.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…[34][35][36][37][38] In the TPIAT literature, one small study showed a universal increase in thrombopoietin a few days after surgery, followed by a marked platelet count rise. 16 The data presented here in association with the IBMIR and thrombopoietin production physiology described above suggest that the observations of nearly universal post-TPIAT thrombocytosis likely occurs through both increased proinflammatory platelet production and postsplenectomy mechanisms. 16 Previous work has examined the utility of drugs like heparin, 21 lowmolecular-weight dextran sulfate, 22,39 and melagatran 33 in TPIAT but primarily evaluated whether they reduce IBMIR and thus improve islet survival.…”
Section: Discussionsupporting
confidence: 51%
“…Hematologic outcomes including TE and thrombocytosis and management strategies for each have only recently been examined, despite this procedure's long history. 13,15,16,26 In this retrospective review of a large contemporary TPIAT cohort containing both pediatric and adult patients, we examined ExT and TE to determine their rates, potential links to portal vein measurements, and the success of current mitigation strategies. Pediatric and adult patients differed notably in terms of platelet trends, TE, and pharmacologic strategies to manage thrombocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total pancreatectomy with islet autotransplantation is a complex but potentially curative surgery for debilitating chronic or acute recurrent pancreatitis, with a few unique side effects. Extreme thrombocytosis frequently occurs postoperatively and is hypothesized to be because of in part a combination of splenectomy, inflammatory response to infusion of islets into the portal vein, and increased thrombopoietin levels 6,7,32–34 . In some pediatric centers that perform this surgery, including ours, hydroxyurea is started for platelet cytoreduction and aspirin for antiplatelet therapy in an effort to reduce postoperative portal vein thrombosis risk.…”
Section: Discussionmentioning
confidence: 99%